PERANCANGAN WEB APLIKASI AKREDITASI PADA SEKOLAH MENENGAH KEJURUAN ATAU MADRASAH - Hardinata, Rian (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
School Accreditation is the one of activity that BANSM (Badan Akreditasi Nasional Sekolah dan Madrasah) do often, one of many thing to do when School Accreditation happen is taking a conclusion based upon two opinion of accreditation officer, before, they are do this manually, this behaviour make Accreditation take too much time to finish.Furthermore, the data processing software didn’t save the data at the database, the software cannot provide a backup whenever there’s a situation which needed to take the data back. Thats why the web application of accreditation build to solve the problem, this web application could store and process the data of accreditation officer answer and make that data into a report, this web application also could make a conclusion based on knowledgebase, this process happens using forward chaining method.